Strategi Pemimpin dalam Meningkatkan Budaya Organisasi yang Islami - Darmawati Darmawati (UIN Antasari Banjarmasin, 2022)
There's been a lot of talk lately about the leadership crisis. This happens not only within the scope of the organization, but also the leaders of a region and even a country.We can judge that the conventional management system is seen as unsuitable for a government institution or an organization in Indonesia because of many shortcomings and weaknesses. One management that has been proven to be good starting from the time of the Prophet Muhammad is to apply Islamic management. If the leader already has the qualities and concepts of the leadership of the Prophet Muhammad, then the organization will be easy to run in accordance with Islamic management and easy to shape the quality of human resource management that is guided by the totality of Islamic life which is strategic in the context of developing a complete Islamic environment, namely faith and piety to Allah SWT, professional, intellectual, disciplined and efficient.